2019
DOI: 10.1111/1752-1688.12784
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Retrospective National Water Model Streamflow with Respect to Droughts and Low Flows in the Colorado River Basin

Abstract: Streamflow monitoring in the Colorado River Basin (CRB) is essential to ensure diverse needs are met, especially during periods of drought or low flow. Existing stream gage networks, however, provide a limited record of past and current streamflow. Modeled streamflow products with more complete spatial and temporal coverage (including the National Water Model [NWM]), have primarily focused on flooding, rather than sustained drought or low flow conditions. Objectives of this study are to (1) evaluate historical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…As a result, the NWM currently only considers a one‐way flux, where groundwater can enter a stream but cannot return to the aquifer. Previous studies have evaluated the NWM prediction performance and found that the NWM overpredicts streamflow in many cases, but the causes of this overprediction are not fully understood (Johnson et al 2017; Hansen et al 2019). Many of the studies that have evaluated the NWM’s performance have primarily focused on flood inundation mapping which requires accurate streamflow predictions, but these studies do not directly evaluate the streamflow prediction ability of the model (Afshari et al 2018; Zheng et al 2018; Johnson et al 2019; Shastry et al 2019) In this study we aim to directly evaluate the NWM’s streamflow prediction ability.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the NWM currently only considers a one‐way flux, where groundwater can enter a stream but cannot return to the aquifer. Previous studies have evaluated the NWM prediction performance and found that the NWM overpredicts streamflow in many cases, but the causes of this overprediction are not fully understood (Johnson et al 2017; Hansen et al 2019). Many of the studies that have evaluated the NWM’s performance have primarily focused on flood inundation mapping which requires accurate streamflow predictions, but these studies do not directly evaluate the streamflow prediction ability of the model (Afshari et al 2018; Zheng et al 2018; Johnson et al 2019; Shastry et al 2019) In this study we aim to directly evaluate the NWM’s streamflow prediction ability.…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge on the streamflow thresholds is important when making decisions with respect to planning, design and management, but it becomes critical when mathematical models are calibrated and verified for the purpose of generating streamflow to evaluate critical scenario [26]- [28]. Hence it is prudent to determine "watershed hydrology driven streamflow thresholds" to properly plan and perform the tasks of water resources management [13], [19].…”
Section: Eng (Prof) Ntswijesekera C Eng Fie(sri Lankamentioning
confidence: 99%
“…There is also the continued concern regarding the restricted abilities of hydrologic models to provide a good forecasting performance partly because of the difficulty in carrying out a meaningful evaluation of the model components and parameter fields [11], [12]. At the same time, most objective functions and models are capable of satisfactorily reproducing a specific part of the streamflow spectrum [13]- [15].…”
Section: Introductionmentioning
confidence: 99%
“…They present an approach that seems to improve the accuracy of inundation mapping in the study area. Hansen et al (2019) evaluated NWM performance during low flows and drought conditions. Their study focused on comparing NWM predictions against streamflow measurements in the Colorado River Basin (CRB).…”
Section: Overviewmentioning
confidence: 99%
“…Hansen et al () evaluated NWM performance during low flows and drought conditions. Their study focused on comparing NWM predictions against streamflow measurements in the Colorado River Basin (CRB).…”
Section: Overviewmentioning
confidence: 99%